Hand Hygiene and Sanitation Behaviour in Rural Prayagraj District of Uttar Pradesh (International Journal of Food and Nutritional Sciences, 2022)
Background: The main mode of transmission of the COVID-19 virus is respiratory and contact so frequent hand washing with soap under running water for at least 20 seconds is recommended by WHO. In this research paper, an attempt has been made to show the kind of change has taken place in the knowledge, attitude and practice of people on hand washing in rural Uttar Pradesh after COVID-19. Objectives: To examine the knowledge, attitude and practice of the people on hand washing in rural Prayagraj District of Uttar Pradesh. Methods: Two stage stratified random sampling method was followed for the selection of two Blocks, 20 villages and 600 respondents in Prayagrag, Uttar Pradesh. Respondents above 18 years of age were interviewed for the study to assess the existing knowledge, attitude and practice on the hygiene and sanitation. Results: Hygiene is one of the important components of the study. Therefore, it was found in the study that 77.3 percent respondents wash their hands first by plain water. Analysis indicates that all of respondents wash their hands in one form or other thereby reflecting washing hands is well established practice in the villages. In all households where the interview was conducted a set of five observations were made in which it was observed that hand washing place was established only in 36.7 percent households. Conclusion: People in the rural areas are not following necessary sanitation, hygiene and health related practices because of their own habits. Lack of awareness, poor economic condition, low education, and poor water supply, lack of space and age old habit are the major hurdles people are not following proper sanitation, hygiene and health related practices in their houses.